Assessment of the Kidney Size in Newborns - Mandana Kashaki; Ladan Younesi; Marjan Esmaeili; Hasan Otoukesh; Mohammad Esmaeili (Reviews in Clinical Medicine, 2017)
Introduction: Ultrasonographic assessment of the kidney size in newborns is essential to the diagnosis of renal diseases during the neonatal period. According to the literature, altered renal dimensions may lead to changes in the kidney echotexture in certain renal pathologies. This systematic review aimed to evaluate the renal dimensions in premature and term neonates.Methods: This systematic review was conducted to identify the English articles on the renal dimensions of children and premature/term neonates via searching in databases such as PubMed, Google Scholar, and Scopus. In total, 74 studies were retrieved from the electronic databases. After reviewing the titles and abstracts, 10 articles that were in line with the study objectives were selected in full text and evaluated.Result: The studies on the renal dimensions of newborns had been performed on various populations. Some studies had compared kidney diameters with the body weight and length of the neonates within the first days of birth, while some others had compared the gestational age of neonates with their kidney size. However, no conclusive results were proposed. In addition, several studies were found on kidney size during the fetal period and childhood, while limited investigation was available regarding the neonatal period. In the present study, we analyzed the correlations between the renal dimensions of neonates and their gestational age, length, weight, and body surface area by reviewing the current literature.Conclusion: Although renal volume is considered to be the most precise index of the kidney size, renal length is evidently the most practical indicator of renal dimensions, which is correlated with the anthropometric indices and gestational age of neonates.